2018
DOI: 10.1002/pat.4357
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced corrosion protection performance with MWCNT dispersed epoxy coating prepared under supercritical CO2 assistance

Abstract: The corrosion protection performance of epoxy coatings could be enhanced by incorporation of nanofillers such as MWCNT. However, a homogeneous dispersion of MWCNT in epoxy polymer is still a teasing challenge. Herein, we report an environmentally benign single‐step supercritical CO2 processing method to improve the dispersion of MWCNT in epoxy matrix in order to achieve an effective anticorrosive coating. The executed approach provides a cluster‐free uniform distribution of MWCNT in epoxy matrix as characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…Thus, solid epoxy resin has unique advantages in storage, transportation, and processing technology, and important application value in multiple fields. The waste rate of solid epoxy resins by the powder coating process is nearly close to 0%, and the amount used is significantly less than the other solvent‐based resin adhesives to achieve the same bonding strength . Therefore, solid epoxy resins have great development potential and application value as environment‐friendly thermosets.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, solid epoxy resin has unique advantages in storage, transportation, and processing technology, and important application value in multiple fields. The waste rate of solid epoxy resins by the powder coating process is nearly close to 0%, and the amount used is significantly less than the other solvent‐based resin adhesives to achieve the same bonding strength . Therefore, solid epoxy resins have great development potential and application value as environment‐friendly thermosets.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating MWCNTs in EP-amine influences and redistributes the water hydrogen bonding states, resulting in a reduced corrosion rate. Khanam et al 24 studied the corrosion protection performance of MWCNT/EP coatings prepared by the supercritical CO 2 processing method. Results showed that the uniform dispersion of MWCNTs in the EP matrix reduced the porosity of EP coating and improved the impermeability of corrosive ions.…”
Section: Introductionmentioning
confidence: 99%
“…to facilitate construction, which is extremely unfriendly to the environment by releasing harmful organic solvents and volatile substances. With the imposition of legislative restrictions on the emission of organic solvents to the atmosphere, the solvent-free solid epoxy resin has aroused much attention in recent years [5][6][7][8] due to excellent environment-friendly characteristics, 6 notable efficient utilization 9 and convenience. 8 In addition, solid epoxy can be rapidly cured at moderate temperature in several minutes, 10 thus helping to save energy on industrial production.…”
Section: Introductionmentioning
confidence: 99%